(untitled) (New York, 2003)
From the leading authors in the field, Michael Moran, Howard Shapiro, Bruce Munson, and David DeWitt, comes an integrated introductory presentation of thermodynamics, fluid mechanics, and heat transfer. The unifying theme is the application of these priciples in thermal systems engineering. Responding to pressures to reduce credit hours in the curriculum and to ABET-inspired objectives for more integrated treatment of engineering topics, this text surveys the field of thermal sciences with an emphasis on applications to thermal systems engineering. The authors have identified the critical subject areas needed for analysis of thermal systems, and provided them in a text of manageable size. A flexible organization gives instructors choices in the coverage they provide their students.
Keywords: Thermodynamics,Nhiệt động lực học